2020
DOI: 10.1016/j.parepi.2020.e00177
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent infection of intestinal parasites and Helicobacter pylori among school-age children in Central Ethiopia

Abstract: Background Coinfection of multiple intestinal microbial pathogens plays an important role in individuals harboring these organisms. However, data on magnitude and risk factors are scarce from resource limited settings. Objective We examined the prevalence and associated risk factors of intestinal parasites and Helicobacter pylori co-infection among young Ethiopian school children. Method Data from a total of 434 Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Concurrent infection of H. pylori and intestinal parasites was reported in a number of studies [31,32,[49][50][51][52][53] . Under normal conditions, gastric juice creates an unfavorable medium for pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent infection of H. pylori and intestinal parasites was reported in a number of studies [31,32,[49][50][51][52][53] . Under normal conditions, gastric juice creates an unfavorable medium for pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…And this response can vary depending on the species of protozoa or helminths and can probably vary with the stage of their life cycle (intestinal phase or migration phase). It is wellknown that H. pylori infection as well as Giardia promotes the Th1 immune response, whereas helminths increase the Th2 immune response and thus, the IL-4 level was increased in the group with coinfection by H. pylori and helminths [3,4,9,10].…”
Section: Serum Interleukin-4 (Il-4) Levels In the Gastroduodenal Disorders (Gdd) Group In Relation To Infections With Helminths Giardia Omentioning
confidence: 97%
“…The study in Colombia has shown that the frequency of H. pylori co-infection with A. lumbricoides in children aged 1-6 years varied 9-89% depending on the region and climate [18]. The study conducted in central Ethiopia found that 23% of school-age children were coinfected with H. pylori and any intestinal parasite while 18.7% were co-infected with H. pylori and any protozoa, but the incidence of enterobiasis (1.4%) or ascariasis (0.2%) was also low [9]. We suggest that it is necessary and important to continue assessing the frequency of co-infection by H. pylori and intestinal helminths in symptomatic and asymptomatic children of different ages in Ukraine.…”
Section: Serum Interleukin-4 (Il-4) Levels In the Gastroduodenal Disorders (Gdd) Group In Relation To Infections With Helminths Giardia Omentioning
confidence: 99%
See 1 more Smart Citation
“…Soil transmitted helminths are one of the most frequent infections in the world, affecting an estimated 3.5 billion people and infecting 450 million people [1]. These infections are a major public health concern because they induce anaemia due to iron deficiency, growth retardation in children, and other physical and mental health issues [2,3,4]. Ascaris lumbricoides, Trichuris trichiura, Enterobius vermicularis, and Hookworms are pathogenic intestinal protozoans that infect the small and/or large intestine and harm people in tropical countries [5].…”
Section: Introductionmentioning
confidence: 99%